Visual search for hazardous items: using virtual reality (VR) in laypersons to test wearable displays for firefighters - Feder, Sascha; Püschel, Aline; Şimşek, Melis; Odenwald, Stephan; Bendixen, Alexandra; Einhäuser, Wolfgang (Frontiers in Virtual Reality, 2024)
In virtual reality (VR), we assessed how untrained participants searched for fire sources with the digital twin of a novel augmented-reality (AR) device: a firefighter's helmet equipped with a heat sensor and an integrated display indicating the heat distribution in its field of view. This was compared to the digital twin of a current state-of-the-art device, a handheld thermal imaging camera. The study had three aims: (i) compare the novel device to the current standard, (ii) demonstrate the usefulness of VR for developing AR devices, (iii) investigate visual search in a complex, realistic task free of visual context. Users detected fire sources faster with the thermal camera than with the helmet display. Responses in target-present trials were faster than in target-absent trials for both devices. Fire localization after detection was numerically faster and more accurate, in particular in the horizontal plane, for the helmet display than for the thermal camera. Search was strongly biased to start on the left-hand side of each room, reminiscent of pseudoneglect in scene viewing. Our study exemplifies how VR can be used to study vision in realistic settings, to foster the development of AR devices, and to obtain results relevant to basic science and applications alike.